Already Doing It : Intellectual Disability and Sexual Agency - Gill, Michael Carl (Book collections on Project MUSE., 2015)
"Why is the sexuality of people with intellectual disabilities often deemed 'risky' or 'inappropriate' by teachers, parents, support staff, medical professionals, judges, and the media? Should sexual citizenship depend on IQ? Confronting such questions directly, Already Doing It exposes the 'sexual ableism' that denies the reality of individuals who, despite the restrictions they face, actively make decisions about their sexual lives. A powerfully argued call for sexual and reproductive justice for people with intellectual disabilities, Already Doing It represents a vital new contribution to the ongoing debate over who, in the United States, should be allowed to have sex, reproduce, marry, and raise children"--